Perlindungan Hukum Terhadap Pengguna Game Online Atas Sistem Monetisasi Lootbox Di Tinjau Dari Pasal 1320 ayat 4 dan Pasal 1337 - Roman Agustian Hasan; Mutia Cherawaty Thalib; Dolot Alhasni Bakung (Jurnal Mahasiswa Kreatif, 2023)
This study aims to determine legal protection for online game users over the lootboox monetization system in a positive legal perspective in Indonesia, based on the title raised in this study. This research uses the type of normative juridical research. The process of collecting data from the objects studied in this study is using primary, secondary, and tertiary techniques. The data obtained by this research uses a qualitative method which explains the relationship between variables and generalizes the social phenomena studied. The results of this study indicate that several formulations of laws and regulations that can help stabilize and defend rights and obligations from a civil perspective regarding the issue of the Lootboox Monetization System as well as in the case of the Lootboox Monetization System are inseparable from legal consequences and forms of accountability from parties who violate a law. agreement and also there are several suggestions about how the Lootboox Monetization System should be run nowadays.